Anticoagulation in Neonatal ECMO: An Enigma Despite a Lot of Effort! - Cashen, Katherine; Meert, Kathleen; Dalton, Heidi (Frontiers in Pediatrics, 2019)
Extracorporeal membrane oxygenation (ECMO) is a valuable modality used to support neonates, children, and adults with cardiorespiratory failure refractory to conventional therapy. It requires use of anticoagulation to prevent clotting in the extracorporeal circuit. Balancing bleeding from excessive anticoagulation with thrombotic risk remains a difficult aspect of ECMO care. Despite many advances in ECMO technology, better understanding of the coagulation cascade and new monitoring schemes to adjust anticoagulation, bleeding and thrombosis remain the most frequent complications in ECMO and are associated with morbidity and mortality. In neonates, ECMO is also complicated by the immature hemostatic system, laboratory testing norms which are not specific for neonates, lack of uniformity in management, and paucity of high-quality evidence to determine best practices. Traditional anticoagulation focuses on the use of unfractionated heparin. Direct thrombin inhibitors are also used but have not been well studied in the neonatal ECMO population. Anticoagulation monitoring is complex and currently available assays do not take into account thrombin generation or platelet contribution to clot formation. Global assays may add valuable information to guide therapy. This review provides an overview of hemostatic alterations, anticoagulation, monitoring and management, novel anticoagulant use, and circuit modifications for neonatal ECMO. Future considerations are also presented.